Hubungan Kejadian Laten Tuberkulosis dengan Kontak pada Pasien Tuberkulosis - Hadiyanto (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2020)
Introduction: Latent TB is still a problem in Indonesia, the absence of symptoms in patients with latent TB makespatients feel they don't need treatment. Aim of study: The purpose of this study was to analyze the relationship oflatent TB incidence with TB contact patients. Method: This study uses research data on the role of gammainterferon as a marker of the effectiveness of the BCG vaccine, the sample in this study has a complete examinationrecord, especially IGRA examination, then the data are analyzed by the Chi squre method. The total sample was 421respondents. Results and Discussion: Based on the results of the study of female respondents was 265 (62.9%), withan age range of 21-40 were 186 (44.2%) respondents, Positive IGRA 123 (29.2%) respodents, patient contact withTB patients was 105 people, and no contact history with TB patients was 316 people. The prevalence of latent TBwas 29 percent, while respondents who have a history of contact with tuberculosis patients about 33.3 percent andwithout a contact history of 27.8 percent. Conclusion: From the results of the analysis, there was no significantrelationship between latent tuberculosis events and contact history with tuberculosis patients (P value 0.284).Therefore, further research needs to be done to include variables that have not been included in the beginning suchas economic factors, respondent nutrition, and conduct a re-examination to determine the current health status ofrespondents.